The 'pole-hooking' method: A novel and economical technique for in situ tagging small to medium-sized fishes - Irigoyen, Alejo Joaquin (2008)
We describe a new manual procedure for catching and tagging fish underwater, the 'pole-hooking' method, and demonstrate and discuss its advantages over standard tagging techniques (i.e. hook-and-line fishing). The new technique was designed for tagging Acanthistius brasilianus [Cuvier, M., Valenciennes, L.B., 1828. Histoire Naturelle des Poissons. Museau de Histoire Naturelle, Paris], a small to medium-sized fish inhabiting rocky reefs of the Argentine coast. The pole-hooking method minimizes injuries, avoids fast depressurization of fish and allows registration of the precise location of capture and release. In addition, the equipment needed is very simple and economical. The mean number of fish tagged per minute using this methodology on shallow rocky reefs (up to 25-m depth) was similar to that obtained during hook-and-line fishing sessions (ca. one tagged fish every 3 min), given similar densities of A. brasilianus in the fished reefs.